Technical communication - Markel, Michael H.; Selber, Stuart A. (Boston : Macmillan Education, 2018)
This book helps you make the leap from writing in college to writing in workplace settings. Full of clear, practical advice and real-world examples from a range of sources, this text helps you develop the kinds of writing processes and documents that you'll encournter on the job. -- Provided by publisher.
Includes bibliographical references (pages 698-706) and indexes.
Keywords: Technical writing; Communication of technical information; Communication of technical information; Technical writing